Development of E-Servqual Dimensions for Banking - Emilia Sindi (Soegijapranata Catholic University, 2024)
E-SERVQUAL is a tool used to measure customer service quality. This research aims to conduct a literature review on the dimensions and indicators of service quality specifically used for digital banking services. The research method has 3 stages, namely : First, Planning contains the Explanation of Research Objectives, Second, Research Identification contains the Determination of Criteria and Selection of Research Articles, Third, Selection of Basic Studies contains Selection of research articles using predetermined criteria keywords. The keyword used is